2019
DOI: 10.1186/s13019-018-0825-3
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications after thoracic endovascular aortic repair. Does the left subclavian artery coverage without revascularization increase the risk of neurological complications in patients after thoracic endovascular aortic repair?

Abstract: IntroductionOne of the most severe complications after TEVAR is ischemic stroke and spinal cord ischemia (SCI) resulting in severe disability. These complications can be fatal up to 30% of cases, so it is very important to define risk factors associated with the occurrence of such events. The aim of this study was to define the causes and risk factors associated with the occurrence of neurological complications in patients after TEVAR.Materials and methodsWe performed a retrospective analysis of 51 patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Several studies are suggestive that revascularization is beneficial [ 1 , 7 , 8 ]. Other’s counter-argue that there are is no statistical differences [ 9 12 ]. Our study favors the former for the reason that there was a higher incidence of 30-day SCI in unrevascularized group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies are suggestive that revascularization is beneficial [ 1 , 7 , 8 ]. Other’s counter-argue that there are is no statistical differences [ 9 12 ]. Our study favors the former for the reason that there was a higher incidence of 30-day SCI in unrevascularized group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies are suggestive that revascularization is bene cial 1,7,8 . Other's counter-argue that there are is no statistical differences [9][10][11][12] . Our study favors the former for the reason that there was a higher incidence of 30-day SCI in unrevascularized group.…”
Section: Discussionmentioning
confidence: 99%
“…50 Nonetheless, a recent observational study showed nonsignificant association between LSA revascularization and SCI (p = .58) or stroke (p = .37) incidence in patients undergoing TEVAR. 51 Other less commonly reported postprocedural complications include acute myocardial infarction, left upper limb ischemia, acute kidney injury, malperfusion, access-related pseudoaneurysm, or groin hematoma. 38,51 Aorta-specific TEVAR-related complications including retrograde type A aortic dissection (RTAD) and stent F I G U R E 3 Kaplan-Meier curve for overall survival of 156 uncomplicated type B aortic dissection patients retrospectively reviewed between 2000 and 2014, shown for false lumen diameter.…”
Section: Tevar Risks and Risk Mitigationmentioning
confidence: 99%